Nanomedicines targeting activation of STING to reshape tumor immune microenvironment and enhance immunotherapeutic efficacy - Chen, Shanshan; Peng, Anghui; Chen, Muhe; Zhan, Meixiao (Frontiers in Oncology, 2023)
Immunotherapy has greatly enhanced the effectiveness of cancer treatments, but the efficacy of many current immunotherapies is still limited by the tumor-suppressive immune microenvironment. Multiple studies have shown that activating the stimulation of IFN genes (STING) pathway and inducing innate immunity can significantly impact the tumor immune microenvironment and improve antitumor therapy. While natural or synthetic STING agonists have been identified or developed for preclinical and clinical use, small molecule agonists have limited utility due to degradation and lack of targeting. As such, the delivery and release of STING agonists into tumor tissue is a major challenge that must be addressed in order to further advance the use of STING agonists. To address this challenge, various nanomedicines have been developed. In this paper, we concisely review the antitumor immunotherapeutic mechanisms of STING agonists, highlighting the latest developments in STING agonists and the current progress of nanomedicines for activating STING. We classify the different nanomedicines according to the STING agonists they utilize in order to facilitate understanding of recent advances in this field. Finally, we also discuss the prospects and challenges of this field.